The Effect of Operational Costs on Sales at Mujur Jaya Photocopy Business in Pandan, Central Tapanuli Regency - Berli Anni Br Siburian; Rifka Hadia Lubis; Hadijah Sipahutar (Devitara Innovations, 2025)
This study aims to analyze the effect of operational costs on sales at the Mujur Jaya Photocopy Business in Pandan. This research employed a quantitative approach using simple linear regression analysis. The data used were secondary data obtained from the business financial reports during the 2020–2024 period, which included operational cost components such as paper costs, ink or toner expenses, electricity costs, machine maintenance, and employee salaries, as well as sales data. The results of the study indicate that operational costs have a positive and significant effect on sales. The coefficient of determination (R²) value of 0.845 indicates that 84.5% of the variation in sales can be explained by operational costs, while the remaining 15.5% is influenced by other factors outside the research model. The t-test results show a significance value of 0.000 (< 0.05), indicating that the hypothesis stating that operational costs significantly affect sales is accepted. In addition, the classical assumption tests confirm that the data are normally distributed and that the regression model is appropriate for analysis. The study concludes that effective and efficient management of operational costs plays an important role in increasing sales, maintaining business sustainability, and strengthening the competitiveness of the photocopy business.